Sustainable River Water Treatment Using Coffee Grounds: A Case Study on the Batanghari River - Raudhatussya'rifah, Ra'ida; Heraningsih, Sarah Fiebrina; Alfernando, Oki; Widyastuti, Nita; Amelia, Dera; Meiyola, Nada Karima; Amanda, Nathasya Putri; Sakinah, Syarri; Ancel, Violetta Fanissa (Universitas Trunojoyo Madura, 2025)
The Batanghari River is increasingly contaminated by organic and inorganic pollutants resulting from intensive human activities, posing significant risks to both ecosystems and public health. This study evaluates the potential of spent coffee grounds—a low-cost, eco-friendly organic waste—as a biosorbent to purify the river water, specifically focusing on the removal of soluble contaminants measured by Total Dissolved Solids (TDS). The coffee grounds were prepared via thermal activation (110 °C for 30 min) and systematically tested in a batch adsorption system using dosages of 1, 2, and 3 grams to determine the optimal dosage for water quality improvement. The treatment demonstrated high efficacy across multiple water quality parameters. The adsorbent achieved an outstanding turbidity removal efficiency of 91.96%, effectively eliminating suspended particles. The optimal reduction in TDS was recorded at 4.9 mg/L using the 3-gram dosage, confirming success against soluble contaminants. Concurrently, the pH level increased from 6.65 to 8.16 at the 2-gram dose, reflecting improved water neutrality, and physical observations confirmed the murky, foul-smelling water became visibly clearer and odorless. Isotherm analysis revealed that the adsorption process is governed by the Langmuir model, confirming a favorable monolayer adsorption mechanism. This is evidenced by a maximum adsorption capacity (Qmax) of 10.50 mg/g and a separation factor (RL) of 0.21. These results robustly establish spent coffee grounds as a highly accessible and sustainable solution for environmental remediation, offering a viable pathway for restoring river water quality while utilizing agricultural waste.